Superseding the Seamstress — The Sewing Machine, from Invention to Mass Production in a Generation. (July 2014) - Gregory, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> The industrialization of the cloth production into large factories came in the eighteenth century. However, making cloth into clothes remained a hand operation until the mid-nineteenth century. The invention of the sewing machine evolved from significant technical innovation by many workers, producing stitches that could not be made by hand. Alongside innovation in business practices such as the Patent Combination, Hire Purchase and Part Exchange, the sewing machine industry inaugurated major advances in 'interchangeable manufacture'. To produce the millions of cheap machines, each containing many small precision parts, required its own machine tool revolution.